ANALISIS KEDUDUKAN HUKUM DALAM ALQURAN (Suatu Analisis Keadilan dan Kemanusian) - Firdaus, Firdaus (DIKTUM: Jurnal Syariah dan Hukum, 2012)
The Qur'an not only regulates human vertical relationship with God, but also set the horizontal human relationships with each other and with the natural surroundings. The number of verses in the Quran the law only slightly compared with the governing creed. Verses such laws are generally global, in tune with the dynamics of a society that is always dynamic, growing and changing. The concept of the law of the Koran integrating between justice and humanity, which is reflected in the implementation of the punishment like any concepts valuable humanitarian obligations. The concept of justice and humanity in the law is essentially a objectives of Islamic law.